Investigation for macro mechanical behavior explicitly for thin-walled parts of AlSi10Mg alloy using selective laser melting technique. (June 2021) - Zhang, Yingfeng; Majeed, Arfan; Muzamil, Muhammad; Lv, Jingxiang; Peng, Tao; Patel, Vivek
Abstract: Recently additive manufacturing of aluminum alloys by selective laser melting (SLM) is of research interest due to its potential benefits in manufacturing industries. The present work investigates the SLM-built AlSi10Mg thin-walled parts and their macro-mechanical behavior in correlation with relative densities. The superlative mechanical behavior of SLM parts was achieved by using the optimal parameters, i.e. 320 W of laser power, 900 mm/s of scanning speed, and 80 μm of hatch distance. The results showed that the SLMed AlSi10Mg thin-walled specimens attained the highest relative density of 99.86 % and 99.21 % for the wall thickness of 0.50 mm and 5.0 mm, respectively. For 0.50 mm wall thickness specimen, the tensile strength of 250.9 MPa, yield strength of 143.7 MPa, breakage elongation of 5.31 %, and microhardness of 116.8 HV were attained which would be comparable to those of the conventionally die-cast A360 alloy. The 364 MPa of tensile strength and 12.04 % of breakage were achieved for 5.0 mm thin-walled specimen. The fracture behavior of different thin-walled fabricated tensile specimens was also examined using a scanning electron microscope (SEM).